Alfabetização científica por meio da criação de jogos digitais do tipo RPG - GOMES , Dandara Nyegilla Silva (2020)
Science teaching aims, in addition to understanding concepts, training for citizenship. In this sense, science curricula and pedagogical proposals aim to promote Scientific Literacy or Scientific Literacy, as is the case with the Common National Curriculum Base. Despite the variation of terms, with regard to what should be taught in science education, both Literacy and Scientific Literacy cover aspects in common: on the one hand, the understanding of conceptual scientific knowledge and, therefore, the application of that knowledge of critical and reflective way, an aspect that is directly related to the Science, Technology and Society approach. Among the possible strategies used to raise these aspects, we highlight in this research the creation of digital games. We proposed and applied a Didactic Sequence that aimed to promote Scientific Literacy through the creation of digital games with a focus on chemistry content and a socio environmental issue, on the RPG Maker game creation platform. The necessary subsidies for the production of the games were due to the discussion of a problem situation whose central theme was air pollution caused by fires. To identify the evidence of the process of Scientific Literacy in the episodes of the Didactic Sequence, we used the methodological tool Indicators of Scientific Literacy of Cerati (2014), adapted according to the specificities of this research. In order to understand which factors influenced the manifestation of these indicators, we analyzed the process from the perspective of Wertsch's Theory of Mediated Action (1991, 1998). This research was carried out with nine students from the 1st grade of high school in a state school in the city of Bacabal-MA. The analysis of the data allows us to infer that the creation of digital games constitutes a potential cultural tool in teaching strategies that aim at Scientific Literacy. The production of meanings from the creation of the games was evidenced by the Scientific Literacy indicators expressed both in the plots and in the games as a final product and in all the episodes that constitute the Didactic Sequence. In the light of the Theory of Mediated Action, we found that social interactions mediated by cultural tools contribute substantially to the process of producing meanings in science, that is, Scientific Literacy.